2019
DOI: 10.1007/s40368-019-00424-w
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of delivery of dental care and dental pathologies in children and young people with osteogenesis imperfecta

Abstract: Background Osteogenesis imperfecta (OI) is the most common inherited disorder of bone fragility in children, increasing fracture risk 100-fold and can feature dental and facial bone involvement causing additional morbidities. Aim To assess the utilisation of tertiary dental services by children and young people with OI attending a supra-regional multidisciplinary OI service and review of the pathology identified and interventions undertaken. Design Case notes review of the current caseload of children and youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Of 15 unique records (4 abstracts, 11 full texts) [ 13 , 30 , 33 – 45 ], most included children ( n = 7, 46.7%); fewer records including adults or mixed populations were identified ( n = 4, 26.7% each). Records described the utilisation of services ( n = 10) [ 13 , 30 , 36 – 41 , 45 , 46 ], experience with services ( n = 3) [ 35 , 41 , 42 ], progression through the healthcare system ( n = 2) [ 33 , 35 ] and interactions with specific healthcare professionals or consultants ( n = 9) [ 13 , 33 – 37 , 41 – 43 ]. While many records described ante- and postnatal care ( n = 4) (39) [ 40 , 45 , 46 ], occupational and physical therapy ( n = 4) [ 37 , 41 – 43 ] and multidisciplinary care approaches ( n = 5) [ 13 , 33 – 35 ], fewer records described dental care [ 36 ] and outpatient care ( n = 1 each) [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of 15 unique records (4 abstracts, 11 full texts) [ 13 , 30 , 33 – 45 ], most included children ( n = 7, 46.7%); fewer records including adults or mixed populations were identified ( n = 4, 26.7% each). Records described the utilisation of services ( n = 10) [ 13 , 30 , 36 – 41 , 45 , 46 ], experience with services ( n = 3) [ 35 , 41 , 42 ], progression through the healthcare system ( n = 2) [ 33 , 35 ] and interactions with specific healthcare professionals or consultants ( n = 9) [ 13 , 33 – 37 , 41 – 43 ]. While many records described ante- and postnatal care ( n = 4) (39) [ 40 , 45 , 46 ], occupational and physical therapy ( n = 4) [ 37 , 41 – 43 ] and multidisciplinary care approaches ( n = 5) [ 13 , 33 – 35 ], fewer records described dental care [ 36 ] and outpatient care ( n = 1 each) [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Clark et al reported the real-life challenges in referring individuals with OI to a tertiary dental clinic for further assessment, with the main barrier being geographic factors and need of extra travel. 23 In addition, individuals with OI usually have relatively short neck and some extent of immobility, which makes routine dental examination even more challenging. 5 This underscored the advantage of joint assessment in a combined multidisciplinary clinic with orthopaedic surgeons, paediatric endocrinologist/paediatric bone specialist, geneticist and dental specialists of oral and maxillofacial surgeon and orthodontist.…”
Section: Discussionmentioning
confidence: 99%
“…However, it could be challenging practically. Clark et al reported the real-life challenges in referring individuals with OI to a tertiary dental clinic for further assessment, with the main barrier being geographic factors and need of extra travel 23. In addition, individuals with OI usually have relatively short neck and some extent of immobility, which makes routine dental examination even more challenging 5.…”
Section: Discussionmentioning
confidence: 99%
“…Osteogenesis imperfecta (OI) is a rare heterogeneous group of connective tissue disorders characterized by increased fragility of the bony tissue. [1] Its estimated frequency in the general population is about 1 in 15.000 to 20.000 new-borns [2,3]. Most patients have dominant mutations in one of two genes, COL1A1 and COL1A2, which code the collagen type I synthesis [4,5].…”
Section: Introductionmentioning
confidence: 99%